CFD simulation for the optimal design and utilization of experiment to research the flow process in PWR. (August 2016) - Chen, Guangliang; Zhang, Zhijian; Tian, Zhaofei; Dong, Xiaomeng; Wang, Yafeng
Highlights: The effect of the region boundary and region size in experiment has been studied. Some regularities on the flow characteristics in experiment have been found. The guidance for the optimal design and utilization of an experiment has been obtained. Abstract: The Pressurized Water Reactor (PWR) has numerous complex and narrow structures, such as a spacer grid, mixing vane, and narrow channels. Experiments can be used to research the flow characteristics in a reactor. However, using some simplification and approximation cannot be avoided: for example only several fuel rods are used and some solid walls are imposed for modeling the flow in a reactor core. The influence of these simplifications needs to be considered and discussed clearly, since the influence certainly exists and it may result in errors. To obtain a good understanding, this research has studied the impact created by the experimental conditions. The regularities found in this research can be used as a guide for the optimal design and utilization of an experiment to study the physical processes in a PWR.